Development of Low Cost Toxic Gas Explosive Modeling System using Wireless Array Sensor Netwok. (November 2018) - Setyohadi, D P S; Riskiawan, H Y; Kautsar, S; Destarianto, P
Abstract: The Natural disasters such as floods, earthquakes, erupting volcanoes and toxic gases affect life can even result in permanent ecosystem and environmental changes. Monitoring of toxic gases is one of the important issues, it is based on the nature of the gas that is difficult to detect movement, especially in large areas. Ijen crater reportedly began spewing toxic gas on March 21, 2018, and poisoned 30 people who lived in four villages on the slopes of Mount Ijen. This study aims to develop a tool with an array sensor application that is able to adapt to environmental conditions. This detection device providing 24hour surveillance of toxic gases. In the application, the sensors will be placed in areas affected by toxic gas disasters, it aims to provide early warning if there is a toxic gas wave from Mount Ijen. It is also able to give warning to visitors and prospective visitors of Mount Ijen. So that ultimately no longer found victims of toxic gas, or at least reduce the impact of this toxic gas disaster.